The challenges of digitalization of civil justice: towards a flexible orality - Michele Angelo Lupoi (Revista Ítalo-Española de Derecho Procesal)
Small claims proceedings are increasingly characterized by the prevalence of writing over orality. EU Regulation No. 861/2007 provides for proceedings that reduces but does not eliminate oral and direct contact between parties and judge. The author considers it appropriate to enhance this flexible orality, also making use of the tools of digital proceedings.